(untitled) (International Journal of Applied Research in Management and Economics, 2020)
Customer loyalty is a serious matter of concern for every business where it measures the customer’s likeliness to give repeat business with a brand or organization. In other words, it is the outcome of a positive experience for customers as well as customer satisfaction. In this paper, the role of the relational dimension will be studied in the context of customer loyalty. The aim of this paper is to analyze the concept of relationship marketing and the key variables of the dimension relationship and their role in customer loyalty. South Asian telecommunication industry is selected to analyze the role of relational dimension in the context of customer loyalty. Previous studies will be reviewed to analyze the concept of relationship besides demonstrating the role of relationship marketing in the telecommunication industry. Additionally, the concept of customer loyalty and multiple theoretical approaches to customer loyalty is appropriately discussed here. Another important part of this study is that this paper will discuss the different phases of loyalty. The primary research will be accomplished through a questionnaire survey method and the collected data will be analyzed with statistical analysis. A positive relationship between the elements of relationship marketing and customer loyalty is analyzed through multiple correlations and regression tables. It shows that all the components of relationship marketing have a good impact on customer loyalty and will prove that more customers will confident more they will be loyal to the brand.